Comparative analysis of network performance using network traffic analyzer tools in FSKM laboratory - Zoraidi, Nur Huda; Mohd Yusof, Mohd Azahari; Abdul Rahid @ Abdul Rashid, Nurul Najwa (College of Computing, Informatics, and Mathematics, 2025)
In today’s world, academic and operational excellence depend on reliable network connectivity. However, there are several challenges that delay user productivity due to inconsistent Wi-Fi performance and bottlenecks. The aim of this project is to evaluate four network traffic analyzer tools which are Wireshark, Acrylic Wi-Fi Analyzer, TamoSoft Throughput Test and Iperf3 through experiments during and outside teaching and learning sessions to address the challenges. Some key network performance metrics include latency, throughput and packet loss that were analyzed to determine tool accuracy and reliability under various traffic conditions. The methodology involved a testbed consisting of three laptops connected to the UiTM Wi-Fi Student network. The data was collected from different levels and sessions to highlight how performance can be influenced by infrastructure and user density. Wireshark was the best tool that could consistently perform, achieving the lowest latency of 0.57 ms and minimal packet loss 0.2% during outside teaching and learning sessions. While Acrylic Wi-Fi Analyzer recorded up to 92 ms latency, TamoSoft Throughput Test showed the highest throughput of 12.82 Mbps while packet loss pointed to 11.5%, indicating limitations under heavy load. On the other hand, Iperf3 recorded the lowest throughput values as low as 1.08 Mbps in controlled conditions. These results highlight the importance of tools selection based on specific network need while emphasizing the importance of Wireshark for critical environments. This project provides insight into further improvements in academic network performance to ensure better connectivity along with operational efficiency.